Penentuan Alokasi Buffer Untuk Meningkatkan Performansi Lini Produksi (Studi Kasus di PT. General Electric Lighting Indonesia) - I Wayan Suletra; Muh. Hisyam; Sigit Prasetyo (Performa: Media Ilmiah Teknik Industri, 2007)
PT. GE Lighting Indonesia is a manufacturing company that producing lamp. In generally, PT. GE Lighting Indonesia’s producing line consists of 5 machines with buffer allocation storage between machine that have early capacity of buffer1= 1225 units, buffer2= 915 units, buffer3=820 units, and buffer4=545 units. The allocation of these buffer is definetely done with purpose to place output from machine before processed to the next machine. Time difference process in every machine make the stream of production process become less fluent and affecting less maximal throughput. Other cause that making the throughput of production line process less maximal is machine damage factor. Although the preventive maintenance policy is applied in PT. GE Lighting Indonesia remain to be the machine damage cannot be obviated at production process take place. This research will try to redetermine the buffer allocation in PT. GE Lighting Indonesia in order to make the production process more fluent, so that can increase the throughput in production line. The method that is use to redetermine the buffer allocation is simulation approach. The reason why the author use this method is because there wasn’t found a representative and valid analytical model that match with the system.The simulation is done with Promodel 4.0 software. Based on the experiment design and running of simulation, it’s achieved a conclusion that the best alternative buffer capacity is at 900 units (buffer1, buffer2, buffer3, buffer4 has a same capacity at 900 units) with average throughput at 9.651 units/shift. While in the early buffer capacity only produce as many as 9.207 units/shift. Finally, if it’s compared with the early condition, redetermining the buffer allocation can increase the throughput of production line process equal to 444 units/shift.